السلوك العدواني لدى الأطفال( مفهومه وأشكاله ومظاهره وأسبابه والنظريات المفسرة له) (Comprehensive Journal of Science, 2025)
This study aimed to identify aggressive behavior in children, in terms of its concept, forms, manifestations, causes, and theories explaining it. The researcher followed the inductive and deductive method, which relies on reviewing previous theoretical literature to collect data and information. This method is one of the most important methods used in qualitative studies. The importance of this study stems from the fact that it addresses a behavioral problem known as aggressive behavior, which has increased in our time and has negative effects on the individual, the family, and society alike. Through this study, the researcher concluded that aggressive acts are nothing but a result of the various environmental changes that occur at all levels and aspects that constitute this environment, as a result of human interaction with it through giving and receiving. It is as if reality is saying that the defacement of public property today is nothing but a reaction to what has happened at the social levels that make up our Arab societies. The problem of aggressive behavior is considered one of the problems that has become a source of anxiety for individuals in society due to its negative effects on all age groups, as it affects the stages of individual development. Therefore, it is necessary to Parents should give their child complete freedom to express their opinion in order to establish their presence and express themselves, and surround them with affection, love, and tenderness to achieve healthy adjustment to themselves and others. Based on the researcher's findings on the study topic, the following recommendations and suggestions were presented.
Keywords: Aggressive behavior and children